2003
DOI: 10.1021/jp022481+
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Drying Step in the Preparation by Impregnation of Zn/SiO2 Supported Catalysts

Abstract: Zinc supported over silica materials, which are widely used in heterogeneous catalysis, are prepared in most cases by incipient wetness impregnation with solutions of zinc nitrate. After calcination, the formation of ZnO is usually assumed, although not always fully demonstrated. The goal of this paper is to clarify the nature of the zinc phase present in Zn/SiO 2 samples not only after calcination, but also after drying. To achieve this goal, the supported zinc phase was characterized in such systems after dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…Chemical homogeneity of the particles at a nanoscale level was checked by EDX microanalysis using a FEG (Field Emission Gun) -TEM equipment (probe diameter: 4 nm) operating also at 200 kV and EELS measurements, using a Scanning Transmission Electron Microscope (STEM) operating at 100 kV (probe diameter: 0.5-1 nm) and equipped with a parallel EELS spectrometer optically coupled to a CCD camera. Cationic distribution was inferred from EXAFS at 10 K at the Zn and Fe K-edges and from XCMD at 4 K at the Fe L 2,3 -edges measurements according to the general procedures described in the literature [7,8].…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Chemical homogeneity of the particles at a nanoscale level was checked by EDX microanalysis using a FEG (Field Emission Gun) -TEM equipment (probe diameter: 4 nm) operating also at 200 kV and EELS measurements, using a Scanning Transmission Electron Microscope (STEM) operating at 100 kV (probe diameter: 0.5-1 nm) and equipped with a parallel EELS spectrometer optically coupled to a CCD camera. Cationic distribution was inferred from EXAFS at 10 K at the Zn and Fe K-edges and from XCMD at 4 K at the Fe L 2,3 -edges measurements according to the general procedures described in the literature [7,8].…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Several strategies have been proposed to prevent metal agglomeration during the thermal treatment of ex-nitrate catalyst precursors. These include careful tuning of heating rate and temperature profiles [31,33,34], and the use of glow-discharge plasma-assisted nitrate decomposition [35]. The gas-solid hydrodynamics has also a significant impact on the resulting metal dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that our findings are in satisfactory agreement with the so far observed PL bands. On the other hand, only Chouillet et al [14] observed and proved the minor ZnO phase in the synthesized zinc silicate. They also found that the optical absorption could be assigned completely to the minor ZnO phase.…”
Section: Resultsmentioning
confidence: 97%